3‐D printed circularly polarized multibeam antenna array with full azimuth scanning capability and wideband characteristic for 5G millimeter‐wave applications. Issue 9 (7th June 2022) - Ma, Zi Long; Peng, Shao Cong; Chu, Qing‐Xin
Abstract: This paper presents a wideband circularly polarized (CP) multibeam antenna array, which is with full azimuth scanning capability and operates in Ka band for 5G applications. It adopts a circular array configuration and consists of 18 elements with a simple structure. Regarding to each element, it is fed by a 90° bent rectangular waveguide and employs a simplified single dielectric slab polarizer to produce CP waves. Within the axial ratio bandwidth (ARBW), the proposed element can achieve a stable half power beamwidth (HPBW) of 29 ± 7°, while, the 3‐dB AR beamwidth is larger than the HPBW. By switching the active elements, the proposed array can realize 360° beam steering in azimuth plane, while, the HPBW and the 3‐dB AR beamwidth cover the entire plane. To simplify the fabrication process, dielectric and metal 3‐D printing technologies are employed for processing. Experimental results indicate that the proposed array can achieve a 40.5% 3‐dB ARBW which almost covers the entire Ka band from 26.2 to 39.5 GHz and a gain of 9.9 ± 1.5 dBic. The front‐to‐back ratio (FBR) of each beam is higher than 19 dB. In contrast to conventional designs, the proposed antenna features wide band, simple structure, and ease of fabrication.